Family Violence and the Civil Law/Criminal Law Interplay – Some Reflections - Atkin, Bill (Victoria University of Wellington Law Review, 2022)
Family violence is increasingly recognised as a serious social problem. That awareness has led to much legislation being passed to address the problem. The legislation has evolved from distinct civil and criminal roots to a point where the two closely interact. This article explores the sources and consequences of this interplay of the civil and the criminal in relation to family violence. The piece is dedicated to long-time colleague, Professor John Prebble, even though the topic does not grapple with his area of great expertise, the law of taxation.